LPAR1, Correlated With Immune Infiltrates, Is a Potential Prognostic Biomarker in Prostate Cancer - Shi, Jingqi; Jiang, Dongbo; Yang, Shuya; Zhang, Xiyang; Wang, Jing; Liu, Yang; Sun, Yuanjie; Lu, Yuchen; Yang, Kun (Frontiers in Oncology, 2020)
Prostate cancer is a common malignancy worldwide in men. Lysophosphatidic acid receptor 1 (LPAR1) is ancritical gene and it mediates diverse biologic functions in tumor. However, the correlation between LPAR1 and prognosis in prostate cancer, as well as the potential mechanism remain unclear. In the present study, LPAR1 expression analysis was based on The Cancer Genome Atlas (TCGA) and Oncomine database. The correlation of LPAR1 on prognosis was also analyzed based on R studio. The association between LPAR1 and tumor-infiltrating immune cells were evaluated in Tumor Immune Estimation Resource (TIMER) site, ssGSEA and MCPcounter packages in R studio. Gene Set Enrichment Analysis (GSEA) and Gene Ontology (GO) analysis was used to analyze the function of LPAR1. TCGA datasets and Oncomine database revealed that LPAR1 was significantly downregulated in prostate cancer. High LPAR1 expression was correlated with favorable overall survival. LPAR1 was involved in activation, proliferation, differentiation and migration of immune cells and its expression was positively correlated with immune infiltrates, including CD4+ T cells, B cells, CD8+ T cells, neutrophils, macrophages, dendritic cells (DCs) and natural killer (NK) cells. Moreover, LPAR1 expression was positively correlated with those chemokine/chemokine receptors, indicating that LPAR1 may regulate the migration of immune cells. In summary, LPAR1 is a potential prognostic biomarker and plays an important part in immune infiltrates in prostate cancer.